2011
DOI: 10.3109/03091902.2011.629276
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of theex vivobiomechanical properties of porcine cornea with inflation test for corneal xenotransplantation

Abstract: Compared with human corneas, porcine corneas exhibited a similar nonlinear behaviour but lower stiffness values. The biomechanical parameters of porcine cornea obtained from this test could be applied to numerical simulations of refractive surgery procedures and lay a foundation for pig-to-human corneal xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…; Bao et al. ). Our measurement set‐up is basically a combination of stress–strain and stress–relaxation testing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Bao et al. ). Our measurement set‐up is basically a combination of stress–strain and stress–relaxation testing.…”
Section: Discussionmentioning
confidence: 97%
“…; Bao et al. ). Overall, comparability of the different studies dealing with femtosecond laser‐assisted surgeries remains difficult due to the use of several different laser devices, different baseline IOP levels, different test models (human versus porcine; in vivo versus ex vivo ) and different measurement modalities (direct intracameral manometry versus direct intravitreal manometry versus indirect measurements; Kerr et al.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, the association between corneal biomechanical response and IOP has been previously reported in porcine and human eyes ex vivo. Examining 17 porcine eyes under inflation conditions, Bao and colleagues 14 measured the corneal deformation with a laser displacement sensor, estimated Young's modulus of the cornea, and found a linear relationship between Young's modulus and IOP. Elsheikh and colleagues 15 measured the corneal stiffness (expressed in Young's modulus) in 37 human donor corneas using inflation tests and demonstrated that there was a positive linear relationship between Young's modulus and IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, alternatives such as use of synthetic or biosynthetic corneas or use of human stem cells might not represent an alternative for all corneal graft indications . In a such context, porcine corneal xenografts appear as an possible alternative, because the anatomic and biochemical properties of porcine corneas closely resemble those of the human cornea .…”
Section: Introductionmentioning
confidence: 99%